The analysis of scores of athletics competition held at the different times of the day - Abdurrahmanova, C.; Canuzakov, K.; Demirhan, B.; Nigar, Y.; Bolzhirova, E.; Parpibaev, B. (Science, Movement & Health, 2018)
Objective. This research aimed at analyzing scores of competitions of athletes which is held in times closer to training hours and in different times during the same season. 72 athletes including 42 men and 30 women from different branches such as (100 m, 200 m, 400 m, 800 m, 1500 m) shot, high jump, long jump were involved in the research. Methods. In this research the results that athletes who have been training at evening times during the preparatory period gained at competitions held at times that coincide with training hours and at morning hours was recorded. Research data were evaluated in SPSS 15.0 program. Due to the fact that the competition scores are very close to each other datas were converted according to unit of measurement and time. (1 min=60sec), (1 sec=100(cs), (1mt=100 cm). Wilcoxon signed rank test was used because the data showed non parametric property. Results. Statistically significant lower values were found in 100 m and 200 m races of male and female athletes (p <0,05) and at 400 m races that are held only among male athletes in times closer to training hours. Conclusions. According to these results, it can be concluded that, planning the training hours of explosive athletes according to competition hours may positively effect the competition scores.